High response rate and acceptable toxicity of a combination of rituximab, vinorelbine, ifosfamide, mitoxantrone and prednisone for the treatment of diffuse large B‐cell lymphoma in first relapse: results of the R‐NIMP GOELAMS study. (21st May 2013) - Gyan, Emmanuel; Damotte, Diane; Courby, Stéphane; Sénécal, Delphine; Quittet, Philippe; Schmidt‐Tanguy, Aline; Banos, Anne; Le, Steven; Lamy, Thierry; Fontan, Jean; Maisonneuve, Hervé; Alexis, Magda; et al.
Summary The optimal management of relapsed diffuse large B‐cell lymphoma (DLBCL) is not standardized. The Groupe Ouest Est des Leucémies et aAutres Maladies du Sang developed a combination of vinorelbine, ifosfamide, mitoxantrone and prednisone (NIMP) for the treatment of relapsed DLBCL, and assessed its efficacy and safety in association with rituximab (R). This multicentric phase II study included 50 patients with DLBCL in first relapse, aged 18–75 years. Patients received rituximab 375 mg/m² day 1, ifosfamide 1000 mg/m² days 1–5, vinorelbine 25 mg/m² days 1 and 15, mitoxantrone 10 mg/m² day 1, and prednisone 1 mg/kg days 1–5, every 28 days for three cycles. Responding patients underwent autologous transplantation or received three additional R‐NIMP cycles. All patients were evaluable for toxicity and 49 for response. Centralized pathology review confirmed DLBCL in all cases. Toxicities were mainly haematological with infectious events needing hospitalization in nine cases. Two toxic deaths were observed. After three cycles, 22 patients (44%) achieved complete response/unconfirmed complete response, 11 achieved partial response (24%), 2 had stable disease and 13 progressed. The non‐germinal centre B immunophenotype was associated with shorter progression‐free survival. in conclusion, the R‐NIMP regimen displayed significant activity in relapsed DLBCL, with acceptable toxicity and should be considered a candidate for combination with new agents.